Effect of Slow Releasing Versus Conventional FSH Superovulatory Protocol on Superovulatory Response and Embryo Production in Sahiwal Cows - Lalchhanhima, K; Honparkhe, Mrigank; Singh, Narinder; Kumar, Ajeet; Singh Malik, Vijay; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2026)
The conventional superovulation protocols require multiple FSH injections at 12 hours intervals for 4 to 5 days due to short half-life of FSH which results in multiple visits and frequent handling of animals. Thus, the protocols involving multiple FSH dose regimen to induce superovulation adds stress to the animal, increases cost and risk to the handler particularly when the donor cows are not habitual to be handled and have tetchy nature. To overcome these limitations, the present study compared the efficacy of single dose FSH dissolved in aluminium hydroxide gel (Antrin R10 AL) with conventional FSH (Antrin R10) administered in multiple doses in inducing superovulatory response and embryo pro duction in Sahiwal cows. Pluriparous, non-pregnant Sahiwal cows weighing between 400-500 kg having BCS between ≥ 2.5 to 3.5 were administered with estradiol benzoate (@ 2 mg) and progesterone (@ 50 mg/animal) intramuscularly on random day of estrous cycle (Day 0) and CIDR an intravaginal progesterone device were placed on the same day. These cows were randomly allocated into two groups. The group 1 (Antrin R10 group, n=6) were administered with 30 A.U of pFSH divided into 8 equal doses (3.75 A.U. each), intramuscularly starting from day 4 at 12 hourly intervals for 4 days while group 2 (Antrin R10 AL, n=6) were administered 40 A.U subcutaneously once on day 4 of the protocol. The mean number of CL’s were 7.5 ± 2.25 and 7.2 ± 1.82 in group 1 and 2, respectively and did not differ significantly. However, the mean number of embryos recovered (5.8 ± 2.87 vs 1.8 ± 0.48) and the mean number of transferable embryos (4.0 ± 2.14 vs 0.7 ± 0.42, P = 0.158) were numerically higher in the group 1 than in group 2. It was concluded that the slow releasing FSH resulted in lower superovulatory response and embryo production than that of conventional FSH in Sahiwal cows.
Keywords: Antrin; Embryo; FSH; Superovulation; Sahiwal